COVID-19 Dermatological Manifestations in Children - Vladislav V. Ivanchikov; Eduard T. Ambarchyan; Anastasia D. Kuzminova (Union of pediatricians of Russia, 2022)
This article describes various COVID-19 dermatological manifestations that can develop in children. Their incidence and clinical features are described. Chilblain-like lesions were considered as the most typical in children population after coronavirus infection. Description of skin manifestations in multisystem inflammatory syndrome in children is also presented, issues of laboratory diagnosis are covered as well.